Analisis Pengendalian Persediaan Batang Kayu pada Produksi Sekop untuk Meminimalkan Biaya Persediaan - Tria Ayu Oktavia; Siti Muhimatul Khoiroh (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT. ABC is a manufacturing company engaged in shovel production and experiences overstock problems in wooden stick inventory as the main raw material for shovel handles. The ending inventory increased from 3,900 units in January 2025 to 28,273 units in December 2025, while warehouse capacity was only 20,000 units. This condition caused high storage costs and risk of raw material damage. This study aims to analyze the inventory condition of wooden sticks and determine the optimal inventory control policy using the Silver-Meal method. The research used a descriptive quantitative approach with demand, production, ordering cost, holding cost, and warehouse capacity data during January–December 2025. The results showed that the Silver-Meal method produced a more efficient lot size than the current company policy, thereby minimizing inventory costs and reducing raw material overstock in the warehouse.